Developing Cikandung Springs Tourism Through Digital Marketing - Dewi, Kisthi Hanila; Utami, Laisya Arianty; Nurfallah, Hani Oktaviani; Abdi, Lutfi Sukmana; Sudrajat, Riki (Journal of Bussines Management Basic, 2026)
Cikandung Spring Tourism in Cimalaka, Sumedang, has great potential to become a leading tourist attraction. This study aims to analyze destination development strategies through digital marketing to increase attractiveness, information reach, and tourist visits. The research method is descriptive qualitative with observation, interviews, and documentation studies. The results show that digital media such as social media, video platforms, and visual content-based branding can significantly increase the visibility of Cikandung Spring. Content about the beauty of the spring, the natural atmosphere, and visitor experiences is effective in attracting tourists, especially the younger generation. Unfortunately, digital marketing management is not yet optimal due to limited human resources, inconsistent content production, and a lack of collaboration with the local creative community. In addition, there is no structured digital marketing strategy, so the promotional potential has not been maximized. This study concludes that the development of Cikandung Spring tourism through digital marketing has excellent prospects if supported by improved manager competence, consistent branding, and multi-stakeholder cooperation. The implementation of a sustainable digital marketing strategy is expected to strengthen the destination's image while increasing the competitiveness of local tourism in the digital era.